The Role of Abscisic Acid Signaling in Maintaining the Metabolic Balance Required for Arabidopsis Growth under Nonstress Conditions. Issue 1 (9th January 2019) - Yoshida, Takuya; Obata, Toshihiro; Feil, Regina; Lunn, John E.; Fujita, Yasunari; Yamaguchi-Shinozaki, Kazuko; Fernie, Alisdair R.
Abstract : Subclass III SnRK2 kinases play key roles in abscisic acid signaling, which is responsible for maintaining normal metabolism and leaf growth under nonstress conditions. Abstract: Abscisic acid (ABA) is a plant hormone that regulates a diverse range of cellular and molecular processes during development and in response to osmotic stress. In Arabidopsis ( Arabidopsis thaliana ), three Suc nonfermenting-1-related protein kinase2s (SnRK2s), SRK2D, SRK2E, and SRK2I, are key positive regulators involved in ABA signaling whose substrates have been well studied. Besides reduced drought-stress tolerance, the srk2d srk2e srk2i mutant shows abnormal growth phenotypes, such as an increased number of leaves, under nonstress conditions. However, it remains unclear whether, and if so how, SnRK2-mediated ABA signaling regulates growth and development. Here, we show that the primary metabolite profile of srk2d srk2e srk2i grown under nonstress conditions was considerably different from that of wild-type plants. The metabolic changes observed in the srk2d srk2e srk2i were similar to those in an ABA-biosynthesis mutant, aba2-1, and both mutants showed a higher leaf emergence rate than wild type. Consistent with the increased amounts of citrate, isotope-labeling experiments revealed that respiration through the tricarboxylic acid cycle was enhanced in srk2d srk2e srk2i . These results, together with transcriptome data, indicate that the SnRK2s involved in ABA signaling modulate metabolism and leaf growth under nonstress conditions by fine-tuning flux through the tricarboxylic acid cycle.